Study on cold neutron imaging scintillation screen based on glass capillary array filled with Gd2O2S:Tb phosphor - LI Da; TAN Xizao; ZHANG Jilong; XUE Yunfei; LUO Wuxia; JIN Ke; YANG Lifang; WU Zhaohui (He jishu, 2021)
BackgroundAs an excellent nondestructive testing technology, cold neutron radiography is widely employed to image materials of interest in many basic and application research fields. One of key components of such device is the neutron sensitive scintillation screen. Normally, these screens are made up of scintillation or phosphor powder mixed with/without neutron sensing isotopes, such as 6LiF:ZnS(Ag) and Gd2O2S:Tb. Uniform scintillation screens are very difficult to make a trade-off between spatial resolution and neutron detection efficiency. Recently a new type of micro-structural scintillation screens has been proposed, which is expected to have higher spatial resolution while maintaining higher neutron detection efficiency. Following this idea, a scintillation screen has been proposed, developed, and studied by our group.PurposeThis study aims to develop a new type of scintillation screens based on a glass capillary array filled with scintillation powders to achieve high spatial resolution and neutron detection efficiency.MethodsFirst of all, a neutron sensing scintillation screen was made by filling very fine grinded Gd2O2S:Tb phosphor powder into glass capillary arrays. Three main steps, i.e. the phosphor powder grinding, the particle size screening, and the vacuum suction filtration process, were taken making such screens. Then, photographs of Gd2O2S:Tb phosphor before and after grinding were taken with a scanning electron microscope (SEM) to examine the filling efficiency of scintillation powder in the glass capillary arrays. Finally, experimental test of spatial resolution of such scintillation screens was carried out by using an optical system to read out the scintillation light emitted by the screen, and a Siemens Star neutron test target to characterize the screens' spatial resolution with cold neutrons.ResultsX-ray luminescence spectra show that the grinding process reduces the light yield of the phosphor. The filling efficiency of scintillation powder in the glass capillary arrays is up to 70%. The cold neutron imaging system with developed scintillation screen achieves spatial resolution of about 300 μm@CTF=3% by experimental test.ConclusionsAlthough the new neutron sensing scintillation screen is still under-developing and there are still some problems to be overcome, cold neutron imaging scintillation screen based on glass capillary array filled with Gd2O2S:Tb phosphor, proposed in this study, can be used to achieve high spatial resolution and neutron detection efficiency with advantages of low cost and simple fabrication process.